Mini-Extruder for 3D Magnetoactive Polymer Printing - Nina Prem; Dirk Sindersberger; Gareth J. Monkman (Advances in Materials Science and Engineering)
This work describes the development of a new miniature extruder, essential to cavity-free 3D printing of silicone-based smart materials. This makes the 3D printing of magnetoactive and electroactive polymer soft robotic components and devices directly from CAD data possible. The special feature of such an extruder is that it is designed for use with addition-crosslinking RTV-2 silicones, including solid particulate additives. The extruder merges the respective components automatically during extrusion which obviates the need for premixing and vacuum evacuation. Problems associated with inhomogeneities and unwanted cavity production are consequently eliminated. Rheological details necessary to the design, together with some preliminary performance results, are presented.